2014
DOI: 10.1149/2.010405jss
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Dispersion in 〈100〉 Si Nanowire Covered with SiO2Film Calculated by Molecular Dynamics Simulation

Abstract: The phonon dispersion relation in 〈100〉 Si nanowire (SiNW) is calculated by employing a realistic atomistic model surrounded by thin SiO2 layer. We performed molecular dynamics simulations to calculate the dynamical structure factor by the space-time Fourier transform of atomic trajectories, and extracted the phonon dispersion relations. In the SiNWs, low energy phonon branches spread into broad spectra due to the presence of the SiO2 film, which is considered as the origin of the thermal conductivity degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…4. For the oxidized NWs, it is observed that the low energy branches spread into broad spectra, agreeing with our previous MD study [6] . This is due to the presence of SiO2 layer including the SiO2/Si interface [6] , and these low frequency mode must impact on the κ.…”
Section: Resultssupporting
confidence: 92%
“…4. For the oxidized NWs, it is observed that the low energy branches spread into broad spectra, agreeing with our previous MD study [6] . This is due to the presence of SiO2 layer including the SiO2/Si interface [6] , and these low frequency mode must impact on the κ.…”
Section: Resultssupporting
confidence: 92%
“…The resolution was determined by the length of the cell used in the simulation; this length was set to 30a i Å, so as to enable us to discretize the wave number along the [100] direction with 30 steps. 19) The width of one side of a square of the model of 4a i Å was thought to be sufficiently large because we found that the analysis results after changing the width from 4a i to 12a i Å were almost unchanged. Figure 1 shows the unit structure of the bulk Ge 0.75 Si 0.18 Sn 0.07 crystal model.…”
Section: Modeling Proceduresmentioning
confidence: 84%
“…The initial model length and the one side width of square were 30ai and 4ai Å, respectively, because the particular length is set to gain sufficient resolution of the wave number along the <100> direction. The resolution is determined by the length of the cell used in the simulation, and the length of 30ai Å enable us to discretize the wave number along the Γ-X direction with 30 steps (12). Figure 1 shows the unit structure of the bulk Ge0.5Sn0.5 crystal model.…”
Section: Modeling Proceduresmentioning
confidence: 99%